Extending Character Education (PPK) as the Basis for Curriculum Management to Improve the Quality of Learning at SDN 2 Rimo - Bancin, Rika Rosari; Amini, Amini; Akrim, Akrim (PALAPA, 2024)
Character is the "soul" of education as a whole, encompassing all phases of planning, carrying out, supervising, and evaluating instruction. In order to raise the standard of instruction at SDN 2 Rimo, this study tries to explain how curriculum management based on strengthening character education (PPK) is implemented. This study combines a case study methodology with a qualitative approach. While documentation studies were used to gather secondary data, interviews and observation were used to collect primary research data. The study's findings indicate that SD Negeri 2 Rimo's curriculum management program has a significant positive impact on character education that is delivered in the classroom, in the school's culture, and in the community. This is evident from the classroom activities, which include the students' behavior in adhering to the rules and the teacher's increased attention to detail when presenting the lesson plan. Additionally, children have demonstrated excellent attitudes and character in extracurricular activities and are able to interact cordially with peers and parents. Therefore, enhancing character education has a significant impact on raising learning standards.